Dryland Short Season Corn Production in Southeast Kansas - Fausett, Marvin R. (My University, 1995)
This publication outlines the expected costs and returns for dryland short-season corn production in southeast Kansas.
MF993_1995_10
Keywords: MF993; Economics; Crops; MF